2022
DOI: 10.1111/ans.18101
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intermittent compression devices for thromboembolic prophylaxis in major abdominal surgery: a systematic review and meta‐analysis

Abstract: Background: The benefits of mechanical prophylaxis for the prevention of venous thromboembolism (VTE) in abdominal and pelvic surgery are uncertain, with different guidelines stating that graduated compression stockings (GCS) and intermittent pneumatic compression devices (IPCDs) can be used either alone or in combination. To review the efficacy of IPCDs in preventing VTE following abdominal and pelvic surgery. Methods: A systematic review was conducted, identifying relevant literature reporting clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The optimal combination of VTE prophylaxis in major surgery is unknown. Currently, there is no evidence in major surgery to support the use of IPCDs as an adjunct to LMWH and GCSs during and postsurgery 4. Despite this, their use has become commonplace for patients recovering from surgery 5…”
Section: Background and Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…The optimal combination of VTE prophylaxis in major surgery is unknown. Currently, there is no evidence in major surgery to support the use of IPCDs as an adjunct to LMWH and GCSs during and postsurgery 4. Despite this, their use has become commonplace for patients recovering from surgery 5…”
Section: Background and Rationalementioning
confidence: 99%
“…Early comparisons of VTE prevention (usually using unfractionated or LMWH) with a placebo or no intervention were undertaken decades ago, when surgical techniques, anaesthesia, and postoperative management were very different. 4 Enhanced recovery after surgery programmes have changed many aspects of perioperative care for patients undergoing major surgery. Older trials are no longer clinically relevant or applicable.…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Only four studies evaluated major bleeding by International Society on Thrombosis and Haemostasis (ISTH) criteria and these suggested a lower bleeding rate: RR 0.33 (95% CI 0.07 to 1.51) for IPC alone compared with pharmacological prophylaxis. 10 The effectiveness of IPC versus placebo was studied in a recent meta-analysis, 11 in major abdominal surgery. IPC was superior to placebo for the prevention of DVT but did not show superiority over other individual modes of thromboprophylaxis.…”
Section: Thromboprophylaxis With Graduated Compression Stockingsmentioning
confidence: 99%
“…As an additional means of prevention, graduated compression stockings (GCS) and/or intermittent pneumatic compression devices (IPCD) should be worn [ 6 ]. A recent meta-analysis for the use of IPCD in major abdomainl surgery [ 11 ] indicated that IPCDS appear to be efficacious in preventing VTE formation. Their comparative efficacy with respect to other forms of thrombo-prophylaxis is limited and is poorly studied.…”
Section: Introductionmentioning
confidence: 99%